CARDIOSTIMULATION AND RHYTHM DISORDERS IN PATIENTS WITH CHRONIC HEART FAILURE - S. I. Stupakov (Кардиоваскулярная терапия и профилактика)
Chronic heart failure (CHF) is common complication of a variety of cardiovascular diseases. In patients with CHF it common to find atrial and ventricular rhythm disorders. Recently the interest to atrial fibrillation (AF) is growing due to its influence on the prognosis of patients with CHF, combination of CHF with AF has worse outcome comparing to isolated AF or CHF. These patients need to be controlled for their ventricular rate by continuous right-ventricular stimulation. However continuous right- ventricular stimulation leads to worsening of the left ventricle function through complicated mechanisms of synchrony impairment. In dyssynchrony with progression of CHF these patients need cardiac resynchronization therapy. Ventricular rhythm disorders are common in these patients and lead to the increase of death risk, hence such patients need to implant cardioverter-defibrillator, and if with biventricular stimulation there is not only a decrease of death from ventricular arrhythmias, but also decrease of the quantity of onsets of these arrhythmias, so cardiac resynchronizing therapy can prevent AF development in CHF.